2021
DOI: 10.4103/ijo.ijo_2641_20
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged face mask use might worsen dry eye symptoms

Abstract: Purpose: The aim of this study was to explore whether prolonged and consistent face mask use might be associated with worsening of dry eye symptoms in patients with dry eye disease (DED). Methods: Subjects with a previous diagnosis of DED. Their OSDI scores were compared with those recorded in Fall 2019 using the Wilcoxon paired test. Participants were stratified by face mask use: heavy (Group A) or standard (Group B) face mask users. Heavy use was defined as wearing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 12 publications
1
31
0
1
Order By: Relevance
“…We found that there was a significant association of facemask usage with dry eye symptoms, with most participants reporting moderate and severe symptoms. These results agree with another study that found constant facemask use to increase ocular surface disease index (OSDI) scores (Scalinci et al, 2021), and worsening symptoms among contact lens users leading to frequent contact lenses removal after using facemask (Martinez-Perez et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that there was a significant association of facemask usage with dry eye symptoms, with most participants reporting moderate and severe symptoms. These results agree with another study that found constant facemask use to increase ocular surface disease index (OSDI) scores (Scalinci et al, 2021), and worsening symptoms among contact lens users leading to frequent contact lenses removal after using facemask (Martinez-Perez et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…DEDs prevalence in Al-Ahsa, Saudi Arabia, was found to be 32.1% (Alshammari et al, 2021). Risk factors for DED include age, inflammatory diseases, medications (antihistamines, contraceptives), lifestyle and environmental factors (Scalinci et al, 2021). Wearing facemasks has been mandated as one of the measures to control the COVID-19 pandemic.…”
mentioning
confidence: 99%
“…Effects are predominant among more than 6 hours of the digital device use [25]. In a similar study, the comparative OSDI figures taken twice during fall and spring have shown a significant increase in scores among dry eye patients after implementing mask wear, especially 6 hours and five days a week of mask wear [27].…”
Section: Discussionmentioning
confidence: 69%
“…Higher OSDI scores were commonly reported among continuous mask users. It is higher among women than men, higher with existing dry eye disease, and higher among 3 to 6 hours of mask wearers [16,17]. Reduced tear quantity after wearing respiratory PPE, including facemasks and respirators, is also seen.…”
Section: Discussionmentioning
confidence: 99%